Effect of Systemically Administered Amoxicillin and Metronidazole in the Treatment of Chronic Periodontitis - Niraula, Sirjana; Shrestha, Surendra Man; Pradhan, Ameena; Aryal, Shreeya; Shrestha, Shilu (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: Nonsurgical periodontal therapy reduces periodontal inflammation, but complete removal of toxin and bacterial deposits is not always possible. Thus, adjunctive therapeutic strategies like use of systemic amoxicillin and metronidazole have evolved. Objective: To evaluate effect of systemically administered amoxicillin and metronidazole in the treatment of chronic periodontitis. Methods: A pretest post-test study was conducted from February 2021 to November 2021 in Department of Periodontics and Oral Implantology at Peoples Dental College and Hospital after ethical clearance from Institutional Review Committee of PDCH. Thirty-six patients with chronic periodontitis were recruited through convenient sampling. The patients were assigned into two groups meeting the criteria of at least six teeth with probing pocket depth 5-7 mm. Group A received scaling and root planing and Group B received adjunctive systemic Amoxicillin and Metronidazole three times daily for seven days. Clinical parameters were evaluated at one month, three months and six months post-treatment. Data were analysed in SPSS v.20. Results: Mean values of pocket depth (PD), clinical attachment level (CAL), plaque index (PI) and gingival index (GI) were reduced significantly after treatment in both treatment groups with more clinical improvement in adjunctive systemic amoxicillin and metronidazole. However, on intergroup comparison, clinical attachment level and plaque index was not significantly reduced. Conclusions: The findings of the current study showed significant improvements in both groups compared with baseline. Thus, adjunctive systemic amoxicillin and metronidazole provide better results than scaling root planing alone.